Surveillance for Disseminated Gonococcal Infections, Active Bacterial Core Surveillance (ABCs)—United States, 2015–2019 . (28th January 2022) - Weston, Emily J; Heidenga, Brooke L; Farley, Monica M; Tunali, Amy; D'Angelo, Melissa Tobin; Moore, Ashley; Workowski, Kimberly; Raphael, Brian H; Weinstock, Hillard; Torrone, Elizabeth
Abstract: Background: Disseminated gonococcal infections (DGIs) are thought to be uncommon; surveillance is limited, and case reports are analyzed retrospectively or in case clusters. We describe the population-level burden of culture-confirmed DGIs through the Active Bacterial Core surveillance (ABCs) system. Methods: During 2015–2016, retrospective surveillance was conducted among residents in 2 ABCs areas and prospectively in 3 ABCs areas during 2017–2019. A DGI case was defined as isolation of Neisseria gonorrhoeae from a normally sterile site. A case report form was completed for each case and antimicrobial susceptibility testing (AST) was performed on available isolates. Results: During 2015–2019, 77 DGI cases were identified (a rate of 0.13 cases per 100 000 population) and accounted for 0.06% of all reported gonorrhea cases in the 3 surveillance areas. Most DGI cases were male (64%), non-Hispanic Black (68%), and ranged from 16 to 67 years of age; blood (55%) and joint (40%) were the most common sterile sites. Among 29 isolates with AST results during 2017–2019, all were susceptible to ceftriaxone. Conclusions: DGI is an infrequent complication of N gonorrhoeae ; because it can quickly develop antimicrobial resistance, continued DGI surveillance, including monitoring trends in antimicrobial susceptibility, could help inform DGI treatment recommendations. Abstract : During 2015–2019, 77 culture-confirmed disseminated gonococcal infection (DGI) cases were identified through active surveillance for a rate of 0.13 cases per 100 000 population. All available isolates were susceptible to ceftriaxone. Continued DGI surveillance can help inform treatment recommendations.